Portuguese Imperial Building in the Kotte Kingdom of Sri Lanka as a Reflection of 16th Century International Law - Amarasinghe, Punsara (Lampung Journal of International Law, 2023)
The role of colonialism in shaping international law has been a contentious issue among legal scholars, who overwhelmingly view international law as a tool of imperialism. This paper describes the 16th-century interactions between the Portuguese and Sri Lanka, which served as early instances of an international legal system biased towards European interests. The practices adopted by the Portuguese in Sri Lanka during their engagements with the Kotte kingdom represent early instances of unequal treaties, the undermining of sovereignty, and the imposition of "puppet rulers." This paper critically examines these practices in the context of the evolution of international law during the 16th century.